PARTICIPATORY COMMUNICATION OF BEKASI CITY RESIDENTS IN COVID 19 VACCINATION ACTIVITIES - Hamluddin Hamluddin; Tatik Yuniarti; Febrianto Nugroho; Sahrul Budiman; Rizqyututa Primadiansyah (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2022)
It has been argued that the provision of suitable participatory communication can improve people’s participation especially for taking Covid 19 vaccines. The present study aims to analyze the participatory communication of Bekasi local government to reach their goal, making minimum of 30% Bekasi population receiving vaccine. The present study uses a descriptive qualitative approach through observation, interviews and documentation. Four key informants are interviewed while mass messages from the key informants are observed. The results of present study suggest that participatory communication related to the administration of Covid 19 vaccines to Bekasi residents involve Regional Work Units (SKPD) to the lowest local apparatus such as Neighborhood Association (RT) and Citizens Association (RW). Messages are spread using WhatsApp Groups of each RT. In addition, residents who have not taken the vaccine will be encouraged to take vaccines at the nearest vaccination posts.